IN HOUSE TRAINING PENGEMBANGAN RPP PROJECT BASED LEARNING PADA GURU SMK AL MUBAROK GENTENG BANYUWANGI - Rima Trianingsih; Miftahul Jannah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
Project based learning is considered very relevant for vocational school because of some of the advantages possessed, as well as encouraging the increase of skills in students through contextual experiences. Therefore, it is important for teachers at SMK Al Mubarok to have skills to make a project based learning plan. In house training activities are then chosen as a means to create these expectations. In house training is the main goal to provide the concept and practice of making project based learning plan, so that it is ready to be applied in the class. The implementation of in house training activities for the development of project based learning plan on Friday, November 12, 2021 which starts from 7.30 Wib until the completion at SMK Al Mubarok Genteng Banyuwangi. Based on the results of in house training activities, it can be concluded that smk al Mubarok teachers have the competence to developt of project based learning plan. Learning plan results that have been made by teachers will then be applied in the learning process in the classroom in accordance with their respective fields.